2016
DOI: 10.1124/dmd.116.072397
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Intestinal OATP2B1 by the Calcium Receptor Antagonist Ronacaleret Results in a Significant Drug-Drug Interaction by Causing a 2-Fold Decrease in Exposure of Rosuvastatin

Abstract: Rosuvastatin is a widely prescribed antihyperlipidemic which undergoes limited metabolism, but is an in vitro substrate of multiple transporters [organic anion transporting polypeptide 1B1 (OATP1B1), OATP1B3, OATP1A2, OATP2B1, sodium-taurocholate cotransporting polypeptide, breast cancer resistance protein (BCRP), multidrug resistance protein 2 (MRP2), MRP4, organic anion transporter 3]. It is therefore frequently used as a probe substrate in clinical drug-drug interaction (DDI) studies to investigate transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 44 publications
2
29
0
Order By: Relevance
“…For instance, the hydrophilic nature of rosuvastatin requires active uptake transport into the intestinal lumen and is determined by the apically located uptake transporter OATP2B1 and efflux transporter BCRP. 22,50 Interindividual variability of these intestinal proteins could affect the rosuvastatin PKs, and models incorporating intestinal absorption and distribution could shed light on these issues. 22,23 Furthermore, the effect of interindividual differences in hepatic biliary efflux of rosuvastatin, such as transport by BCRP (that was kept constant in this model) could also be of importance.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the hydrophilic nature of rosuvastatin requires active uptake transport into the intestinal lumen and is determined by the apically located uptake transporter OATP2B1 and efflux transporter BCRP. 22,50 Interindividual variability of these intestinal proteins could affect the rosuvastatin PKs, and models incorporating intestinal absorption and distribution could shed light on these issues. 22,23 Furthermore, the effect of interindividual differences in hepatic biliary efflux of rosuvastatin, such as transport by BCRP (that was kept constant in this model) could also be of importance.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, 7 of the clinical inhibitors that caused significant intestinal DDIs (apple juice, ergoloid mesylates, grapefruit juice, naringin, orange juice, quercetin, and ronacaleret) were found to inhibit OATP2B1 in vitro, and 5 (grapefruit juice, green tea, naringin, quercetin, and ronacaleret) were found to inhibit OATP1A2 in vitro. Ronacaleret inhibited OATP2B1 with an IC 50 value of 12 mM in transfected-HEK293 cells, 77 which is slightly over the threshold and, therefore, not presented in Supplementary Table 1. Similarly, quercetin was not included in Supplementary Table 2 because its inhibition parameters were over the threshold, with an IC 50 value of approximately 13.5 mM (substrate: atorvastatin or fexofenadine) and a K i value of 22 mM (substrate: bromosulfophthalein).…”
Section: In Vitro Inhibitors Of Oatp2b1 and Oatp1a2mentioning
confidence: 97%
“…Inhibition of intestinal OATP2B1 can decrease systemic exposure of OATP2B1 substrate drugs without increasing the terminal half‐life. Recent studies showed that ronacaleret, an inhibitor of OATP2B1, decreased rosuvastain plasma exposure by 50% without altering its terminal half‐life …”
Section: New Recommendations For Transporters As Mediators Of Clinicamentioning
confidence: 99%